Progress and prospects of targeted therapy and immunotherapy for urachal carcinoma - Zheng, Yang; Peng, Heling; Hu, Xu; Ou, Yong; Wang, Dong; Wang, Han; Ren, Shangqing (Frontiers in Pharmacology, 2023)
Urachal carcinoma (UrC) is a rare and aggressive disease. Systematic chemotherapy exhibited limited efficacy on patients with advanced disease, and targeted therapy and immunotherapy might provide reasonable alternative for specific population. This review aimed to comprehensively present the molecular profile of UrC and further identify the potential targets for the personalized treatment of UrC as well as the underlying biomarker of immune checkpoint inhibitors. A systematic literature search was carried out by searching the PubMed, EMBASE, Web of Science databases in February 2023 to identify all literature related to targeted therapy and immunotherapy in urachal carcinoma. A total of 28 articles were eligible, and the vast majority of studies included were case report and retrospective cases series And 420 UrC cases were identified to analyze mutational pattern of UrC. The most commonly mutated genes in UrC was TP53 with the prevalence of 70%, followed by KRAS mutations in 28.3 %, MYC mutations in 20.3 %, SMAD4 mutations in 18.2%and GNAS mutations in 18%, while other genes can also be detected. The molecular pattern of UrC and CRC are distinct yet similar. Notably, targeted therapy, especially EGFR-targeting therapy, might provide curative efficacy for patients with urachal carcinoma who bearing specific molecular markers. In addition, either MMR status or PD-L1 expression profile seems to be the potential biomarkers of immunotherapy in UrC.